2017
DOI: 10.1038/ncomms16043
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin directly mediates Epstein-Barr virus immune evasion through binding to G-quadruplexes of EBNA1 mRNA

Abstract: The oncogenic Epstein-Barr virus (EBV) evades the immune system but has an Achilles heel: its genome maintenance protein EBNA1, which is essential for viral genome maintenance but highly antigenic. EBV has seemingly evolved a system in which the mRNA sequence encoding the glycine-alanine repeats (GAr) of the EBNA1 protein limits its expression to the minimal level necessary for function while minimizing immune recognition. Here, we identify nucleolin (NCL) as a host factor required for this process via a direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
182
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(202 citation statements)
references
References 42 publications
8
182
0
Order By: Relevance
“…We therefore designed an experimental strategy that would enable us to detect release of heme from G-quadruplexes by using RNA-Seq analysis to query the effect of treatment with a G-quadruplex ligand predicted to displace sequestered heme on expression of genes involved in heme catabolism and iron homeostasis. We chose to use the well-characterized G4 ligand PhenDC3, a bisquinolinium phenanthroline derivative structurally unrelated to heme (Figure 1A) [De Cian A et al 2007; Piazza A et al 2010; Halder R et al 2012; Chung WJ et al 2014; Perriaud L et al 2014; Lista MJ et al 2017]. PhenDC3 is an ideal compound for genome-wide studies of quadruplex function in vivo , because it readily enters the nucleus [Lefebvre J et al 2017]; it discriminates well between quadruplex and duplex DNA; and it exhibits a very high affinity (nanomolar K d ) for quadruplexes, without pronounced selectivity for any specific quadruplex structure.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore designed an experimental strategy that would enable us to detect release of heme from G-quadruplexes by using RNA-Seq analysis to query the effect of treatment with a G-quadruplex ligand predicted to displace sequestered heme on expression of genes involved in heme catabolism and iron homeostasis. We chose to use the well-characterized G4 ligand PhenDC3, a bisquinolinium phenanthroline derivative structurally unrelated to heme (Figure 1A) [De Cian A et al 2007; Piazza A et al 2010; Halder R et al 2012; Chung WJ et al 2014; Perriaud L et al 2014; Lista MJ et al 2017]. PhenDC3 is an ideal compound for genome-wide studies of quadruplex function in vivo , because it readily enters the nucleus [Lefebvre J et al 2017]; it discriminates well between quadruplex and duplex DNA; and it exhibits a very high affinity (nanomolar K d ) for quadruplexes, without pronounced selectivity for any specific quadruplex structure.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of G4s in viruses and their involvement in virus key steps is increasingly evident in most of the Baltimore groups [10,11]. In the dsDNA group, G4s were described in both Herpesviridae and Papillomaviridae families [12][13][14][15][16][17][18][19][20]. In ssDNA viruses, the presence of G4s was reported in the adeno-associated virus genome [21].…”
mentioning
confidence: 99%
“…The identification of G4s in microbial genomes has opened up new avenues for therapeutics; additional studies on the specificity of G4-binding ligands and their undesired effects may help us to better understand the therapeutic potential of this novel group of antimicrobial agents. Host protein-microbial G4 interaction or the host G4-microbial protein interactions at the molecular interface of the host and microbe during infection are fascinating and merit further investigation [55,56,[66][67][68][69]. It would be interesting to understand if such interactions defend the host or demonstrate yet another mechanism of microbial pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Polysome distribution profiling, in vitro translation, and cell culture experiments identified that formation of quadruplexes obstructs the progress of ribosome machinery, resulting in low levels of EBNA1 and a concomitant decrease in presentation to T cells ( Figure 4D). In addition, nucleolin was identified to bind the G4 formed in the GAr domain of EBNA-1 mRNA [66]. This interaction limits the synthesis of EBNA-1 to levels that allow persistence of the virus and evasion of the host immune system.…”
Section: Role In Virus Latencymentioning
confidence: 99%